Integrating Social Justice Practices into Graduate Training: Collaborating with Stakeholders to Adapt Professional Development in Puerto Rico - Kathryn D Kurtz; Emily R DeFouw; Marta E. Pagan-Ortiz (International Journal of School Social Work, 2021)
Treating trauma has become an international social justice concern, with increasing numbers of graduate training programs prioritizing how to conceptualize needs and interventions within a trauma-informed framework. Minimal research and guidelines exist for adapting these trauma-informed practices for the local community context. Additionally, trauma-informed practices often fail to consider ongoing structural issues faced by oppressed communities such as poverty and racism. Social work, psychology, and counseling graduate training programs often rely on a cultural competency framework instead of a social justice framework that addresses racism and Whiteness. During our graduate Counseling and School Psychology training program at the University of Massachusetts Boston, we collaborated with stakeholders at a school and community center in San Juan, Puerto Rico to culturally adapt and deliver trainings in trauma-informed practices for staff using an ecological validity framework. Using our work in Puerto Rico as a case study, this paper addresses the cultural adaptation of trauma-informed practices and factors to consider when implementing trauma-informed practices, emphasizing the need for creating safety. Strategies for embedding this trauma-informed work into mental health graduate training programs and recommendations for working with individuals from marginalized groups in school settings are discussed.
Keywords: Trauma-Informed Practices; Social Justice framework; Cultural Adaptation; Ecological Validity Framework; Graduate Training; Safety